Survey on the Community Satisfaction Index of Public Services for Provincial Roads: Ahmad Yani Road Section (Pandeglang) and Serang–Pandeglang Road Section (Pandeglang) - Irmayanti; Solihin, Ihin; Yudistira, Yudi; Yunengsih; Alwajir, Dede Qodrat (Neo Journal of economy and social humanities, 2025)
This study evaluates community satisfaction with provincial road services on Ahmad Yani (Pandeglang) and Serang–Pandeglang sections. Using a quantitative approach with 384 respondents determined by the Lemeshow formula, data were analyzed through Importance Performance Analysis (IPA) and Customer Satisfaction Index (CSI). Results show that of 18 service indicators, 9 had positive gaps and 9 negative gaps, with 3 attributes in quadrant I (high importance, low satisfaction). The CSI value of 65.75% indicates users are generally satisfied with the services. Practical implications suggest prioritizing road maintenance, improving responsiveness to user needs, and enhancing accessibility for vulnerable groups. These findings provide useful input for local governments in allocating resources, improving service quality, and developing user centered infrastructure innovations.